Secure Device to Device Communication for 5G Network Based on improved AES - Awlla, Ardalan Hussein; Aziz, Sirwan M. Aziz (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
Communication between two devices (device to device) in network systems can be defined is immediate communication between two devices without crossing the Base Station. Moreover, in a mobile network device to device communication is upcoming communication for the coming generation mobile communication network (5G), 5G is relied upon to permit high network throughput, diminishing communication delays, diminish traffic load and energy consumption. Device to device communication is a core technology of 5G. Therefore, all network types’ security issues must be considered. To deal with the security issue in 5G network we propose an improved Advanced Encryption Standard (AES) with shift row and Mix Columns. The result indicates that the suggested improved AES is more significant than traditional AES.